Impact of tax regulation on the development of financial technology in Indonesia - Jevan Andreas Talahaturusun; Cliff Kohardinata (Journal of Enterprise and Development (JED), 2024)
Purpose — The objective of this study is to assess the influence of recently enacted tax legislation in May 2022 on the advancement of fintech in Indonesia.Method — The present study utilizes a quantitative approach to gather empirical data and conduct hypothesis testing. The population under investigation in this study consists of the total count of lender accounts across 34 provinces in Indonesia, classified according to quarterly periods. The methodology employed in this study involved selecting samples from 33 provinces. Data collection spanned from the second quarter to the fourth quarter of the 2021-2022 period, resulting in a total of 192 observations. The process of hypothesis testing was carried out using multiple regression analysis.Result — The research findings suggest that implementing fintech taxes significantly impacts the number of lender accounts in the following year. This implies that introducing taxes on fintech has a substantial influence on the lending sector, potentially leading to changes in the availability of accounts for borrowers and lenders in the year following the tax adoption.Contribution  — The contribution of this study based on its novelty is that it provides unique insights into the consequences of the recently enacted fintech taxes, which took effect on May 1, 2022. Before this research, no other investigations had explored this specific topic, making this study the first of its kind to shed light on the implications of the regulatory changes within the fintech industry.